Damage identification in underground tunnel structures with wavelet based residual force vector - Wang, S.; Li, Jun; Luo, H.; Zhu, H. (Pergamon, 2019)
Most current studies with vibration-based Structure Health Monitoring (SHM) techniques has been focused on aboveground civil infrastructure. However, a few studies have been conducted for underground structures. The development and application of using dynamic responses measured from underground tunnel structures for condition assessment and damage identification are highly desirable since this may avoid the difficulties in local non-destructive testing in tunnels and improve the efficiency of regular inspections. Since underground tunnel structures are subjected to a more complicated loading and boundary condition, developing reliable and efficient damage identification approach is essential. In this paper, a new damage index based on wavelet based residual force vector to identify damage in a tunnel structure is proposed. Numerical finite element model of a metro tunnel is built and different types of structural damages are introduced at multiple locations of the tunnel. Numerical results demonstrate that the introduced damages can be successfully located. Laboratory tests are further conducted to verify the performance of using the proposed approach for damage identification. A scaled aluminum pipe model which is subjected to the moving train load excitations is placed in a soil box, and experimental dynamic tests are performed for structural damage identification. The feasibility and effectiveness of using this approach for damage identification in tunnel structures are investigated. Damage detection results demonstrate that the proposed damage index can be employed as an efficient and functional damage identification indicator.